Interventional human ocular safety experiments for 222‐nm far‐ultraviolet‐C lamp irradiation - Sugihara, Kazunobu; Kaidzu, Sachiko; Sasaki, Masahiro; Tanito, Masaki (Photochemistry and photobiology, 2025)
The study aimed to directly assess the ocular safety of 222‐nm far‐ultraviolet‐C (UVC) irradiation in humans, given the limited clinical trials in this area. This wavelength offers the potential for safe and effective microbial inactivation in occupied spaces, but its safety profile for human eyes requires thorough investigation. This prospective, interventional study involved five subjects aged 29–47 years, who were exposed to 222‐nm UVC at doses of 22, 50, and 75 mJ/cm2. The subjects were monitored using custom‐made glasses with a UV‐cut filter on one eye to serve as a control. UVC irradiation was conducted using a KrCl excimer lamp, and ocular examinations were performed prior to exposure, 24 h post‐exposure, and at 1, 3, and 6 months. Parameters assessed included visual acuity, refractive error, corneal endothelial density, corneal erosion scores, and conjunctival hyperemia scores. The study found no clinically significant photokeratitis or long‐term eye damage across the five subjects, even at the highest dose of 75 mJ/cm2. Temporary ocular discomfort, including sensations of dryness and epiphora, was reported, but these symptoms subsided within hours after irradiation. The findings indicate that 222‐nm far‐UVC irradiation up to 75 mJ/cm2 does not cause “clinically significant photokeratitis” or long‐term ocular damage, though it may induce temporary discomfort. This supports the safe use of 222‐nm UVC for germicidal applications in occupied environments, providing a basis for revised safety guidelines. To directly assess the ocular safety of 222‐nm far‐ultraviolet‐C (UVC) irradiation in humans, five subjects were exposed to 222‐nm UVC at doses of 22, 50, and 75 mJ/cm2. The findings indicate that far‐UVC irradiation does not cause “clinically significant photokeratitis” or long‐term ocular damage, though it may induce temporary discomfort.